The Effect of COVID-19 Lockdown on Oral Glucose Challenge Tests and Body Mass Indexes in Türk Pregnant Women - Yildiz Akdas Reis; Fahri Burcin Firatligil; Arife Akay; Asya Kalayci Oncu; Yaprak Engin Ustun (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To investigate the glycemic status of pregnant women by the comparison of 50 g glucose challenge test results and body mass index changes in the pandemic period versus last year's test results.